Rekayasa Teknik Guludan sebagai Upaya Rehabilitasi Ekosistem Mangrove di Ekowisata Pantai Alam Serdang Bahari, Pantai Labu, Sumatera Utara - Dian Inda Sari; Nur Subiantoro; Riri Rezeki Hariani; Maya Puspita Ningrum; Abu Salim (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Abrasion at Alam Serdang Bahari Beach (ASB) is increasingly worrying, causing the reduction of mangrove forests on the coast. ASB Beach is located in Regemuk Village, Labu Beach. The ASB Mangrove Forest Farmers Group (KTHM) has made many efforts to continue to exist morally and materially to survive in the ecotourism industry and is trying to re-green the beaches to minimize the impact of abrasion. The results of a field assessment involving lecturers, village officials, and KTHM ASB obtained a roadmap for a sustainable development village with a solution to prevent prolonged abrasion using the simplest and most economical way through engineered bund techniques to protect mangrove plants and also act as a wave breaker. Implementing this PKM aims to make new efforts to plant mangrove trees as coastal abrasion protection. Implementing activities uses a participatory action research (PAR) approach. KTHM, as the partner, carried out the construction of the bund enclosure, and the PKM team was the drafter and supervisor. The results of the PKM implementation are three plots of bunds in the shape of a ship's bow as an effort to break the beach waves using the Rhizopora sp. propagules collected from mangrove seeds by KTHM ASB. This innovation is still early to assess because it requires ongoing monitoring. It is hoped that this effort will better protect newly planted mangrove plants from fierce waves and abrasion as a joint effort to prevent abrasion on ASB Beach.